Oxygen Isotope Composition of the Silicate Minerals and Chrome Ores in the Guleman Ophiolite in Southeastern Turkiye - Erturk, Mehmet Ali; Kara, Hatice; Kalender, Leyla (Maik Nauka/Interperiodica/Springer, 2024)
Oxygen crystallising was obtained from olivine, chromite separates from host rock samples, and gabbro from ultramafic cumulates, harzburgite, and dunite samples collected from tectonites of the Guleman ophiolites. The study includes the oxygen isotope compositions from the Guleman ophiolite and the evolutionary scenarios of geochemical and isotopic signatures. The olivine and chromitite delta(18)Oolivine/chromite and delta(18)Omelt values point out these minerals and melt isotopic compositions similar to mantle values and rich, heavy stable isotopes. The highest delta(18)Ochromite isotopic composition values indicate that as the heavy isotope in the melt increases, the concentration in the mineral increases. Excluding a dunite sample, the values of the delta(18)Owhole rock of the dunite and pyroxenite samples are similar to mantle values. The gabbro samples have higher delta(18)Owhole rock values than the two harzburgites. Hereby, the chromite formations are the later fractional crystallisation products than olivine and dunites due to the lowering of delta O-18. The lower oxygen isotopic composition in studied samples than the normal mantle values, and these values point out subducted hydrothermally alteration. The higher delta O-18 isotopic compositions could be explained by serpentinization on the ocean floor at low temperatures.
Keywords: chromite deposit; Guleman ophiolite; silicate minerals; oxygen isotopes